2022
DOI: 10.1162/jocn_a_01894
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations from Superiors Matter More: Evidence from Behavior and Event-related Potentials

Abstract: As an essential feature of social groups, social hierarchies influence how people interact in daily life. However, it is unknown how external evaluations from peers at different levels in a social hierarchy influence feedback processing. In the current study, participants were instructed to establish a social hierarchy through a novel stick drawing task. With their status in the social hierarchy manipulated to be in the middle, participants received positive or negative evaluations from superiors and inferiors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Based on the previous study having similar variables(Duan et al (2022)), the effect size for the two-way interaction of social hierarchy  valence of feedback on the ERP component of interest is 0.30. 2 Few studies have directly explored the three-way interaction of social hierarchy and the other two within-subject variables on the ERP component.…”
mentioning
confidence: 92%
See 3 more Smart Citations
“…Based on the previous study having similar variables(Duan et al (2022)), the effect size for the two-way interaction of social hierarchy  valence of feedback on the ERP component of interest is 0.30. 2 Few studies have directly explored the three-way interaction of social hierarchy and the other two within-subject variables on the ERP component.…”
mentioning
confidence: 92%
“…Therefore, unfair offers proposed to a superior status recipient would be more unexpected, thus eliciting a stronger FRN. In a study by Duan et al (2022), participants received positive or negative appraisals from superior and inferior status individuals in a stick drawing task, and the ERP results revealed that the P300 increased when the participants received positive (vs. negative) appraisals from the superior status evaluator.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations